The Effectiveness of Safflower Towards Blood Cholesterol Levels Reduction In Menopause of Bontonompo Public Health Centre of Gowa Regency - Sumarni Sikki; Sutrani Syarif (USN Scientific Journal, 2020)
The incidence rate where menopause is more susceptible to an increase in the blood cholesterol levels must be considered by everyone, especially for women; at a certain age, menopause will be more likely to use natural ingredients than synthetic ingredients as a drug. This research aimed to determine the effectiveness of safflowers to reduce blood cholesterol levels in menopause of Bontonompo Public Health Center, Gowa Regency. Methods: This study used a quasi-experimental method with a pretest-posttest only control group design with a sample size of 30 people. Results: Analysis using the Mann Withney statistical test obtained the value of ρ = 0.003 α 0.005, which means that the safflower (Carthamus Tinctorius Linn) is effective in reducing blood cholesterol levels of menopause of Bontonompo Public Health Center. The analysis results using the Mann Withney statistical test obtained the value of ρ = 0.003 α 0.005, which means that the safflower (Carthamus Tinctorius Linn) is effective in reducing blood cholesterol levels of menopause of Bontonompo Public Health Center of Gowa Regency.